2010
DOI: 10.1177/1045389x10367836
|View full text |Cite
|
Sign up to set email alerts
|

Delamination Size Detection using Time of Flight of Anti-symmetric (Ao) and Mode Converted Ao mode of Guided Lamb Waves

Abstract: In this article an attempt has been made to quantitatively assess the extent of delamination in composite laminates, using time-of-flight of fundamental Lamb wave modes, without recourse to baseline data from a healthy structure. An expression has been derived to determine the delamination size, from group velocities of primary Lamb modes in the sub-laminates and time-of-flight of transmitted Ao signal and mode converted Ao signal, which is generated when Ao mode propagates through a delamination. The effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…This confirms that there is no significant change in elastic properties (Young's moduli, shear moduli and Poisson's ratios) of the hybrid laminates in comparison to pristine ones. This observation is in order with the earlier findings [9,20], which report that addition of nanofillers does not influence the elastic properties.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This confirms that there is no significant change in elastic properties (Young's moduli, shear moduli and Poisson's ratios) of the hybrid laminates in comparison to pristine ones. This observation is in order with the earlier findings [9,20], which report that addition of nanofillers does not influence the elastic properties.…”
Section: Resultssupporting
confidence: 93%
“…From the above it is inferred that even though the nanomaterials help in increasing the mechanical strength properties of composites [20] (CNFs in glass/epoxy composite have shown an improvement in compression strength by 40% and interlaminar shear strength by 33%), they result in more attenuation of Lamb wave (A o ). Consequently, distance of propagation of the Lamb wave reduces considerably in a hybridized composite laminate in comparison with its pristine counterpart.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was found that the reflection of the S0 mode from an artificial delamination is strongly dependent on the position of the delamination through the thickness of the laminate [22]. Using the first anti-symmetrical (A0) guided wave mode, the wave scattering at a delamination area was studied both numerically and experimentally, and mode conversion from the A0 mode to the S0 mode observed [23]. From numerical simulations to characterize the scattering pattern generated at a circular delamination, it was found that the amplitudes around a delamination showed a large forward scattered wave relative to the reflected pulse [24].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic inspection is a promising method for characterizing bonding conditions. Lamb waves, which propagate in a plate structure, were used for detecting defects at an interface and succeeded in detecting a relatively large defect compared to wavelength of Lamb waves [1]. Reflection waves at interfaces between an adhesive and adherents owing to acoustic impedance mismatch have also been utilized [2].…”
Section: Introductionmentioning
confidence: 99%